2011
DOI: 10.1172/jci45888
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen years and counting: an update on leptin in energy balance

Abstract: Cloned in 1994, the ob gene encodes the protein hormone leptin, which is produced and secreted by white adipose tissue. Since its discovery, leptin has been found to have profound effects on behavior, metabolic rate, endocrine axes, and glucose fluxes. Leptin deficiency in mice and humans causes morbid obesity, diabetes, and various neuroendocrine anomalies, and replacement leads to decreased food intake, normalized glucose homeostasis, and increased energy expenditure. Here, we provide an update on the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
258
1
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(276 citation statements)
references
References 127 publications
3
258
1
14
Order By: Relevance
“…Circulating leptin shows a diurnal rhythm, peaking in the night in humans. In the models of obesity, leptin resistance can occur and in the absence of leptin's anorexigenic effects, this is accompanied by overeating (reviewed in Gautron & Elmquist (2011)). In humans, acute HFD feeding results in lower 24-h leptin (Havel et al 1999), whereas hyperleptinemia and changes in leptin rhythmicity are observed in obese subjects in accordance with increased fat mass (Considine et al 1996, Rosenbaum et al 1996, van Dielen et al 2002.…”
Section: Leptin and Adiponectinmentioning
confidence: 99%
“…Circulating leptin shows a diurnal rhythm, peaking in the night in humans. In the models of obesity, leptin resistance can occur and in the absence of leptin's anorexigenic effects, this is accompanied by overeating (reviewed in Gautron & Elmquist (2011)). In humans, acute HFD feeding results in lower 24-h leptin (Havel et al 1999), whereas hyperleptinemia and changes in leptin rhythmicity are observed in obese subjects in accordance with increased fat mass (Considine et al 1996, Rosenbaum et al 1996, van Dielen et al 2002.…”
Section: Leptin and Adiponectinmentioning
confidence: 99%
“…Indeed, estrogen action in the hypothalamus increases the local action of leptin (Brown et al 2010), whose catabolic effects in the brain are known to inhibit food intake and increase energy expenditure (Gautron & Elmquist 2011). Moreover, estrogen may regulate energy balance by enhancing leptin-induced activation of the SNS, which innervates the WAT, thereby reducing fat mass through stimulation of SNS-dependent lipolysis (Haifei et al 2009).…”
Section: Estrogen and Melanocortin/leptin-mediated Thermogenesismentioning
confidence: 99%
“…Leptin provides the most robust adipostatic signals, whereas insulin, cholecystokinin, ghrelin, glucagonlike peptide-1 (GLP1), and a number of nutrients act as modulators of the activity of such neurons (4,5,6,7).…”
Section: Introductionmentioning
confidence: 99%